Intestinal Duplication and Hirschsprung's Disease: An Extremely Rare and Misleading Combination - Vatta, Fabrizio; Raffaele, Alessandro; Pasqua, Noemi; Brunero, Marco; Pelizzo, Gloria; Avolio, Luigi (European Journal of Pediatric Surgery Reports, 2018)
Hirschsprung's disease and, more rarely, intestinal duplication can both cause intestinal obstruction in neonates. The simultaneous occurrence of these two diseases is reported in only two studies, and in both cases, intestinal duplication was an incidental finding, as it had not determined clinical intestinal occlusion. This paper reports a unique case of coexistence of the two conditions, with both causing intestinal obstruction, delayed appropriate, and definitive surgical treatment.
Keywords: intestinal duplication; Hirschsprung's disease; intestinal occlusion